Decreased atherosclerosis in CX(3)CR1(–/–) mice reveals a role for fractalkine in atherogenesis - Lesnik, Philippe (American Society for Clinical Investigation, 2003)
The hallmark of early atherosclerosis is the accumulation of lipid-laden macrophages in the subendothelial space. Circulating monocytes are the precursors of these “foam cells,” and recent evidence suggests that chemokines play important roles in directing monocyte migration from the blood to the vessel wall. Fractalkine (FK) is a structurally unusual chemokine that can act either as a soluble chemotactic factor or as a transmembrane-anchored adhesion receptor for circulating leukocytes. A polymorphism in the FK receptor, CX(3)CR1, has been linked to a decrease in the incidence of coronary artery disease. To determine whether FK is critically involved in atherogenesis, we deleted the gene for CX(3)CR1 and crossed these mice into the apoE(–/–) background. Here we report that FK is robustly expressed in lesional smooth muscle cells, but not macrophages, in apoE(–/–) mice on a high-fat diet. CX(3)CR1(–/–) mice have a significant reduction in macrophage recruitment to the vessel wall and decreased atherosclerotic lesion formation. Taken together, these data provide strong evidence that FK plays a key role in atherogenesis.